Peningkatan Kemampuan Komunikasi Bahasa Inggris di Era Globalisasi kepada Para Pemuda Karang Taruna di RW 05 Desa Karang Asem Barat–Citeureup Kabupaten Bogor - Bejo Sutrisno; Suhendar Suhendar; Mohamad Mansur; Budiarto Budiarto; Mukhlasul Fasikh (Jurnal Abdimas Prakasa Dakara, 2021)
The objectives of this study are (1) to train participants in good and correct English communication both grammatically and in correctly choosing the right words and (2) to train fluency in English communication to understand the skills in each component which consists of listening exercises, the use of proper and correct language structures in writing, reading comprehension, and speaking proficiency. The method used is a communicative approach method that trains students to understand the skills in each training component which consists of speaking, writing, reading and listening skills. The results of this activity showed that the training participants experienced positive changes in terms of fluency, understanding, use of language structures and vocabulary.